2018
DOI: 10.3389/fpls.2018.00463
|View full text |Cite
|
Sign up to set email alerts
|

Forest Soil Phosphorus Resources and Fertilization Affect Ectomycorrhizal Community Composition, Beech P Uptake Efficiency, and Photosynthesis

Abstract: Phosphorus (P) is an important nutrient, whose plant-available form phosphate is often low in natural forest ecosystems. Mycorrhizal fungi mine the soil for P and supply their host with this resource. It is unknown how ectomycorrhizal communities respond to changes in P availability. Here, we used young beech (Fagus sylvatica L.) trees in natural forest soil from a P-rich and P-poor site to investigate the impact of P amendment on soil microbes, mycorrhizas, beech P nutrition, and photosynthesis. We hypothesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 78 publications
3
32
0
Order By: Relevance
“…The beech saplings from natural rejuvenation used in our experiment were of similar age to those investigated by Yang et al (2016) and Zavišić et al (2018). In contrast to the strong influence of "current soil" on the N, Mg, and K concentrations in the second year, P concentrations in different plant compartments were still similar to P concentrations of saplings from the two sites when grown in their natural soil (Zavišić et al, 2018).…”
Section: Availability Of Nutrients In the Soil And Plant Nutritional mentioning
confidence: 61%
See 3 more Smart Citations
“…The beech saplings from natural rejuvenation used in our experiment were of similar age to those investigated by Yang et al (2016) and Zavišić et al (2018). In contrast to the strong influence of "current soil" on the N, Mg, and K concentrations in the second year, P concentrations in different plant compartments were still similar to P concentrations of saplings from the two sites when grown in their natural soil (Zavišić et al, 2018).…”
Section: Availability Of Nutrients In the Soil And Plant Nutritional mentioning
confidence: 61%
“…Comparing foliar nutrient concentrations and nutrient ratios with threshold values by Mellert and Göttlein (2012); ratios) and Göttlein (2015); concentrations in mature trees), the mature beeches at BBR exhibited a balanced nutrition except for a latent deficiency in K and N/K ratios above the normal range, while the trees at LUE showed a latent deficiency in P and N/P, N/Mg, and N/Ca ratios above the normal range. A lower P nutritional status of juvenile beech trees from LUE than from BBR was documented by Zavišić et al (2018). They found a respective difference in P concentration for all plant compartments.…”
Section: Availability Of Nutrients In the Soil And Plant Nutritional mentioning
confidence: 92%
See 2 more Smart Citations
“…Numerous studies confirmed that P addition influenced fine root biomass, leaves and litter‐fall quantity and quality, tree growth, aboveground primary production, the rate of succession for plants and for microbial phototrophs, soil nutrient status, soil microbial biomass, and community composition . Collectively, the direction and magnitude of P addition on these variables range from negative to positive.…”
Section: Introductionmentioning
confidence: 95%